Mike and Psmith, - Wodehouse, P. G. (Pelham Grenville), 1881-1975 (Meredith Press, 1969)
Gloomy when his poor scholastic record forces him to change schools just as he is about to become captain of the cricket team, an English boy cheers up when he discovers another new boy in similar circumstances.